Data management in biodiversity / Kho Soon Jye - Kho, Soon Jye (2014)
Biodiversity describes the variety of life found on Earth and it is a broad area to explore. In this field, a huge amount data has been collected by researchers. Thus, it is essential to manage those information with usage of computerized software, e.g. database. A database that stores biodiversity information is known as biodiversity database. Malaysia is one of 17 mega-diversity countries. Its rich biodiversity has important economic, technological and social implications to the nation. In 16th April 1998, Ministry of Science, Technology and Environment declared Malaysia‟s national policy on biological diversity, to conserve Malaysia‟s biodiversity and to utilize it in a sustainable manner. The policy listed out 15 action plans and one of those plans encourages the expansion of scientific knowledge base. A database framework is developed to store biodiversity information, along with the construction of information retrieval portal. The framework describes the overall architecture of the system, requirements of system, relational design of database, and user interface design of portal. Using the same framework, three databases were built due to different data schemes. Each database is to store biodiversity information of ginger, fern, and bat species in Malaysia respectively. The database development involves data cleaning and validation on three data files collected from biodiversity experts, followed by the construction of relational database system with the validated data. iv An online information retrieval portal was also constructed using the PHP language. The portal is equipped with fundamental functions: information search function, administrative function and reporting function. The development of the database system is to help researchers systematically and conveniently manage the data, which helps in expansion of scientific base in Malaysia and thus, achieve the policy statement. However, the system developed is introductory and there is still a lot of improvements work could be done. These improvement works will be discussed in this project report, hoping to further increase the effectiveness of system in achieving the objectives.